Serum Phosphorus and Albumin in Patients Undergoing Peritoneal Dialysis: Interaction and Association With Mortality - Huang, Naya; Li, Huiyan; Fan, Li; Zhou, Qian; Fu, Dongying; Guo, Lin; Yi, Chunyan; Yu, Xueqing; Mao, Haiping (Frontiers in Medicine, 2021)
Hyperphosphatemia and hypoalbuminemia confer worse clinical outcomes, whether these risk factors interact to predispose to mortality is unclear. In this prospective cohort study, 2118 incident continuous ambulatory peritoneal dialysis (CAPD) patients were enrolled and categorized into 4 groups based on the changing point regarding mortality at 1.5mmol/L for serum phosphorus and 35g/L for serum albumin. Risks of all-cause and cardiovascular mortality were examined independently and interactively in overall and subgroups. There was no association between serum phosphorus with all-cause and cardiovascular mortality, but significant interactions (P=0.02) between phosphorus and albumin existed in overall population. Patients in subgroup with high phosphorus and low albumin were at greater risk of all-cause (HR 1.95, 95%CI 1.27-2.98, P=0.002) but not cardiovascular mortality (HR 0.37, 95%CI 0.10-1.33, P=0.13), as compared to those with low phosphorus and high albumin. In contrast, patients with both low parameters had a higher risk of all-cause (HR 1.75, 95%CI 1.22-2.50, P=0.002) and cardiovascular mortality (HR 1.92, 95%CI 1.07-3.45, P=0.03). Notably, an elevated risk of both all-cause and cardiovascular mortality was observed in those with low serum albumin, irrespective of phosphorus levels, suggesting low albumin may be useful to identify a higher-risk subgroup of CAPD patients with different serum phosphorus levels.